THE GUT-BRAIN-MICROBIOME AXIS IN CHILDHOOD OBESITY: MECHANISMS AND CLINICAL IMPLICATIONS - Aulia, Bianda; Sundjaya, Tonny (Journal of Indonesian Specialized Nutrition, 2025)
Background: Childhood obesity has become a global health crisis affecting 188 million children aged 5–19 years worldwide, with serious metabolic complications. The gut–brain–microbiome axis has emerged as a key mechanistic link and therapeutic target for obesity in children. Methods: A narrative literature review was conducted using PubMed, Scopus, and Google Scholar and included studies published up to December 2025. Search terms, used in various combinations, included “childhood obesity,” “gut microbiota,” “gut–brain axis,” “targeted interventions,” “probiotic,” and “prebiotic”. Results: Childhood obesity is associated with early-life gut dysbiosis characterized by reduced diversity, higher Firmicutes/Bacteroidetes ratios, and shifts in key taxa, driven by prenatal, postnatal, and lifestyle factors. This dysbiotic microbiota enhances energy harvest, promotes low-grade inflammation and barrier dysfunction, and disrupts gut–brain axis signaling via altered short-chain fatty acids, neurotransmitter, and gut hormone profiles, thereby impairing appetite regulation and favoring positive energy balance. Emerging evidence indicates that targeting the gut microbiota–brain axis with probiotics, prebiotics, synbiotics, and fecal microbiota transplantation may improve metabolic outcomes and body composition in children with obesity. Conclusion: Gut microbiota dysbiosis contributes to childhood obesity via altered metabolism, inflammation, and gut–brain axis–mediated appetite regulation.